The retrospective imagination of A. B. Yehoshua - Haleṿi-Ṿays, Yaʿel (Dimyonot: Jews and the Cultural Imagination, 2020)
Intro -- COVER Front -- Copyright Page -- Table of Contents -- Chapter 1: Condition-of-Israel Novels -- Notes to Chapter 1 -- Chapter 2: Mapping A. B. Yehoshua's Worldview -- Notes to Chapter 2 -- Chapter 3: The Watchman's Stance -- Notes to Chapter 3 -- Chapter 4: Vocation -- Notes to Chapter 4 -- Chapter 5: Holidays -- Notes to Chapter 5 -- Chapter 6: Names -- Notes to Chapter 6 -- Chapter 7: Love Under the Burden of History -- Notes to Chapter 7 -- Notes -- Bibliography -- Index.